Early corticospinal tract damage in prodromal SCA2 revealed by EEG-EMG and EMG-EMG coherence. Issue 12 (December 2017) - Velázquez-Pérez, Luis; Tünnerhoff, Johannes; Rodríguez-Labrada, Roberto; Torres-Vega, Reidenis; Ruiz-Gonzalez, Yusely; Belardinelli, Paolo; Medrano-Montero, Jacqueline; Canales-Ochoa, Nalia; González-Zaldivar, Yanetza; Vazquez-Mojena, Yaimeé; Auburger, Georg; Ziemann, Ulf
Highlights: Corticospinal tract integrity was tested using EEG-EMG and EMG-EMG coherence. SCA2 patients and prodromal SCA2 mutation carriers had reduced EEG-EMG and EMG-EMG coherence. In prodromal SCA2, EEG-EMG and EMG-EMG coherence correlated with predicted time to ataxia onset. Abstract: Objective: Clinical data suggest early involvement of the corticospinal tract (CST) in spinocerebellar ataxia type 2 (SCA2). Here we tested if early CST degeneration can be detected in prodromal SCA2 mutation carriers by electrophysiological markers of CST integrity. Methods: CST integrity was tested in 15 prodromal SCA2 mutation carriers, 19 SCA2 patients and 25 age-matched healthy controls, using corticomuscular (EEG-EMG) and intermuscular (EMG-EMG) coherence measures in upper and lower limb muscles. Results: Significant reductions of EEG-EMG and EMG-EMG coherences were observed in the SCA2 patients, and to a similar extent in the prodromal SCA2 mutation carriers. In prodromal SCA2, EEG-EMG and EMG-EMG coherences correlated with the predicted time to ataxia onset. Conclusions: Findings indicate early CST neurodegeneration in SCA2. EEG-EMG and EMG-EMG coherence may serve as biomarkers of early CST neurodegeneration in prodromal SCA2 mutation carriers. Significance: Findings are important for developing preclinical disease markers in the context of currently emerging disease-modifying therapies of neurodegenerative disorders.